No limiar da incerteza : as relações e condições de trabalho dos assistentes sociais no Espírito Santo - Carletto, Adriana Estela Custódio (2008)
The present study aims at understanding how the changes taken place in the capitalistic society on a local, national and world basis has an impact on the social workers work relations and conditions from Espírito Santo between November 2006 and August 2007.In order to achieve this analysis, we have set this process of production and reproduction of social relations in the center of this debate presenting some of the necessary foundations to elucidate the work dilemmas and the sociability in a time of fetish capital. The concern which leads this study is to facilitate the understanding of this process as an unfinished, historical, complex and dense totality of contradictions. For the achievement of this study we have taken the research data ―The Work Market of Social Workers from Espirito Santo‖ as a base performed by CRSS/17ª Region with a partnership with the Federal University of Espírito Santo and Salesiana and UNIVILA Universities. Two-hundred and two social workers were interviewed, answering questions referred to five points of analysis: professional s profile, institutional insertion; work conditions and relations; professional practice; demands and social policies; militancy and participation. Among this set of questions, our priority was to trace an outline of conditions and relations of work in which the professional activity is performed, beyond the collective construction of history, searching to locate our particularities undertaken by the Social Work in our society. In the data analysis, our greatest challenge was to surpass the plan of immediateness and factualness and to gather theoretical, analytical and empirical substrates which permit to deepen and subsidize the analysis of our study project in the center of a historical process. Our concern was to identify how the Social Work takes part of the process of production and reproduction of social effective relations.